Identification of Potential for Increasing the Business Scale of BUMG Pulo Makmue with the AHP Method - Zakaria, Muhammad; Muhammad Jalil, Saifuddin; Trisna, Trisna; Zuraida, Zuraida (Malikussaleh University, Aceh, Indonesia, 2022)
The village is the lowest regional unit in the state administrative apparatus in Indonesia Indonesia, where the village is currently entering a new era after the birth of the Village Law. Village are expected to become socially, culturally, economically, and politically independent. Village Owned Enterprises (BUMDes) as business and economic institutions is expected to welcome the village community to be more independent, especially in economy. Currently BMUG Pulo Makmue is still facing various obstacles in carrying out its operations, especially in determining business strategies to increase business scale based on priority scales. This study aims to determine the policy priorities that can be taken as a business strategy to increase the Business Scale of BMUG Ulee Makmue. With the increase in business scale, BMUG Pulo Makmue will become an independent and advanced BMUG so that it can meet the expectations of the people of Ulee Pulo Village in terms of improving their welfare. The research was conducted by conducting surveys and collecting data directly in the field while still applying the Covid 19 process. The research method used was the Analytical Hierarchy Process (AHP) analysis to determine the potential for developing study BUMDes in Ulee Pulo Village. The expected result in this study is the potential of Gampong that can be developed by considering the available resources based on a priority scale.